2015
DOI: 10.4028/www.scientific.net/ddf.364.157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Nanocrytalline Surface Modification on Hardness and Microstructural Evolution of Cu-Sn Alloy

Abstract: In this study, a Cu-Sn sintered bronze, used largely for con-rod bushing and automotive transmission, was treated by ultrasonic nanocrystalline surface modification (UNSM). Then, Vickers hardness and microstructural evolution of the treated region were investigated by using scanning electron microscope (SEM), X-ray diffraction (XRD) and transmission electron microscope (TEM). The hardness of the treated surface doubled, which is attributed to the developed of nanoscale grains, deformation twins, and high densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Also, it can be seen that the NG size increased with increasing the depth at the top surface. Li et al have pointed out the possibility of refining grain size of Cu‐Sn alloy by UNSM technique obtained using a cross‐sectional TEM images [9]. They have found that at a depth of about 300 µm from the surface, mechanical twins with dislocations are formed as shown in Fig.…”
Section: Nature Of the Nanostructured Materials Produced By Unsm Tementioning
confidence: 99%
“…Also, it can be seen that the NG size increased with increasing the depth at the top surface. Li et al have pointed out the possibility of refining grain size of Cu‐Sn alloy by UNSM technique obtained using a cross‐sectional TEM images [9]. They have found that at a depth of about 300 µm from the surface, mechanical twins with dislocations are formed as shown in Fig.…”
Section: Nature Of the Nanostructured Materials Produced By Unsm Tementioning
confidence: 99%